PENGARUH PENGGUNAAN MEDIA INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) TERHADAP KETERAMPILAN LITERASI PADA SISWA - Tamami, Abd. Bassith; Nasution, Nasution; Wisnu, Wisnu (Kuttab: Jurnal Ilmu Pendidikan Islam, 2024)
This research aims to evaluate the impact of using Information and Communication Technology (ICT) on students' literacy skills at SMPN 1 Sarirejo, employing an experimental approach with a quasi-experimental design. Data was collected through questionnaires and documentation, then analyzed using validity tests, reliability tests, normality tests, homogeneity tests, normalization gain (N-Gain) tests, and independent sample t-tests. The analysis results indicated a significant difference between classes utilizing ICT and conventional classes regarding students' literacy skills, with the experimental group having higher average scores. The conclusion drawn from this study is that the use of ICT positively affects students' literacy skills.